Skin protective effects of an antipollution, antioxidant serum containing Deschampsia antartica extract, ferulic acid and vitamin C: a controlled single-blind, prospective trial in women living in urbanized, high air pollution area - Milani M; Hashtroody B; Piacentini M; Celleno L (Dove Medical Press, 2019)
Massimo Milani,1 Bita Hashtroody,2 Marco Piacentini,3 Leonardo Celleno31Medical Department, Cantabria Labs Difa Cooper, Caronno P, VA, Italy; 2Cantabria Labs Medical Department, Madrid, Spain; 3Eurofins Cosmetics & Personal Care, ItalyIntroduction: Air pollution causes skin damage and favors skin aging processes such as dark spots and wrinkles, through oxidative stress. Pollutant substances accelerate skin aging through a specific activation of intracellular receptors called AhR (aryl-hydrocarbon receptors). Deschampsia antartica aqueous extract (DAE) has shown to counteract the pollutant-induced AhR activation. Ferulic acid (FA) and vitamin C (VC) are potent antioxidant substances. A serum containing DAE/FA/VC has been recently developed. So far, no clinical data are available regarding the protective actions of this serum against the detrimental effects of air pollution on the skin.Objective: We conducted a prospective, single-blind, 28-day study to assess efficacy and protective effects against air pollution skin damage of a new serum containing Deschampsia antartica extract.Materials and methods: Twenty, photo type I–III, women (mean age 42 years) with at least three dark spots on the face, living in a homogenous urbanized, high pollution area (Rome) were evaluated. The objectives of the study were to evaluate the effects of treatment on skin barrier function, assessed by transepidermal water loss (TEWL) measurement (Tewameter), the effect on dark spots, evaluated by means of colorimetry (Colorimeter CL 400), and the effect on squalene peroxide (SQOOH)/squalene (SQ) skin ratio assessed with face swabs.Results: The trial was conducted between November 20 and December 19, 2018. In comparison with baseline, the product induced a significant improvement of skin hydration (−19% of TEWL), a significant improvement of dark spots (+7%) and a significant improvement of SQOOH/SQ ratio (−16%). The product was evaluated very well by >90% of the treated subjects regarding cosmetic acceptability.Discussion: A serum ...